Implementation of Virtual Reality (VR) and Augmented Reality (AR) in Marketing and Service Development to Increase Customers in the Hospitality Sector - Ahmad Solihin; Siti Nur Azizah; Sutomo Sutomo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This study uses a quantitative approach to evaluate the effect of implementing Virtual Reality (VR) and Augmented Reality (AR) technology on customer satisfaction in the hospitality sector. VR allows customers to tour hotel facilities virtually, while AR adds digital interactive elements that enrich the customer experience. This study used a cross-sectional survey method, with data collected from 200 respondents in four and five-star hotels that have adopted VR and AR technology. A purposive sampling technique was used to select respondents who have used VR and AR-based services in the last three months. Data was collected through a 1-5 Likert scale questionnaire, where the data was analyzed using multiple regression after going through the classical assumption test. The results of the analysis showed that the implementation of VR and AR had a significant effect on increasing customer satisfaction. As many as 72% of respondents stated that virtual tours through VR helped increase booking confidence. In comparison, 64% reported that AR enriched the stay experience with interactive real-time information. This study confirms that VR and AR technologies significantly increase customer engagement and loyalty to hotel services. However, challenges in development costs and technology infrastructure are still obstacles to broader adoption.